Phubbing: Suatu Degredasi Minat Belajar Siswa sebagai Dampak Media Sosial di Mi Dlauul Islam - Khairul Umam; Abu Yazid Adnan Quthny; Choerul Anwar Badruttamam (Journal on Education, 2023)
One outcome of the development and sophistication of man-made science and technology is the internet. It provides many conveniences, social media being one of them. But regrettably, this sophistication affects how well students are educated. Student enthusiasm in learning is starting to decline as a result of the worst possible impact on education that social networking sites might have. This is important because it's possible that the student's motivation to learn is also declining because he cares more about his social network than his academic success. Our users need to be more intelligent in order to reduce the negative effects. Online savvy is the ability to use and handle internet technology responsibly, tailored to needs, and without transgressing moral principles or codes of conduct.